Macro- and micro-mechanical behaviour of a γ′ strengthened Ni-based superalloy at cryogenic temperatures. (1st November 2021) - Jaladurgam, Nitesh Raj; Kabra, Saurabh; Colliander, Magnus Hörnqvist
Graphical abstract: Highlights: Load distribution in a γ ′ strengthened superalloy is measure by in-situ neutron diffraction. The effect of particle size on Load distribution at cryogenic temperatures is studied. Co-deformation of phases leads to intergranular load transfer between in matrix. Coarse γ ′ microstructure experience both intergranular and intragranular load transfer. Coarse particles initially behave elastically but yield at higher stresses. Abstract: In-situ neutron diffraction was performed during tensile deformation of a Ni-based superalloy, Haynes 282, at 20, 100 and 300 K. Two distinct uni-modal microstructures with fine (20 nm) and coarse (200 nm) γ ′ particles were investigated. On the macro-scale yield strength increased and ductility decreased with decreasing temperature, although the most significant decrease in ductility occurred between 100 and 20 K. The work hardening differed between the two microstructures, but was independent of temperature for each microstructure. On the micro-scale intergranular elastic interactions mainly lead to a transfer of the load to grains with the 200 orientation parallel to the tensile axis. No further load re-distribution between matrix and particles occurred in the microstructure with fine γ ′, where shearing of precipitates lead to co-deformation at all temperatures. In the coarse γ ′ microstructure, the load was transferred intragranularly from matrix to particles, in addition to the intergranular load transfer. The particles initially behaved elastically while the matrix deformed plastically, but at higher stresses a change in load partitioning indicated that also the γ ′ phase underwent plastic deformation as a result of the stress build-up from the load partitioning. The tendency for, and effect of, plastic deformation of γ ′ increased with decreasing temperature.